THE IMPACT OF ENVIRONMENTAL CONDITIONS ON MICRO-PHYTOBENTHIC COMMUNITY IN A TROPICAL ESTUARINE ECOSYSTEM - UWADIAE, R.E; NWOKO, J. C. (Nigerian Journal of Fisheries, 2019)
The micro-phytobenthic community structure in the estuarine Lagos Lagoon, South-west, Nigeria was investigated on a monthly basis for six months between May and October, 2016. A range of 7.0 - 300 mg/L, 31.0- 70.0 cm, 6.1 – 8.4, 0.00 – 0.84 mg/L and 0.21 – 5.4 mg/L were recorded for TSS, transparency, pH, nitrate and phosphate respectively. Whereas values obtained for DO ranged from 2.2 to 16.1 mg/L, those of BOD varied between 7.2 and 36.1 mg/L. Four major micro-phytobenthos divisions; Bacillariophyta, Cyanophyta, Chlorophyta and Chrysophyta made up of eight classes, 20 orders, 19 families and 21 genera were recorded in the study area. Bacillariophyta accounted for the highest number of taxa collected and constituted 72% of the total micro-phytobenthos population. The group Cyanophyta accounted for 14% while Chlorophyta constituted 9% of the micro-phytobenthos population. The division Chrysophyta was poorly represented in the study area. Generally, the number of cells of micro-phytobenthos was low and this may have arisen due to the degraded nature of the study area.